Observations and modelling of the global distribution and long-term trend of atmospheric 14CO2 - Levin, Ingeborg; Naegler, Tobias; Kromer, Bernd; Diehl, Moritz; France, Roger J.; Gomez-Pelaez, Angel J.; Steele, L. Paul; Wagenbach, Dietmar; Weller, Rolf; Worthy, Douglas E. (Tellus. Series B, Chemical and physical meteorology, 2010)
Global high-precision atmospheric Δ14CO2 records covering the last two decades are presented, and evaluated in terms of changing (radio)carbon sources and sinks, using the coarse-grid carbon cycle model GRACE. Dedicated simulations of global trends and interhemispheric differences with respect to atmospheric CO2 as well as δ13CO2 and Δ14CO2, are shown to be in good agreement with the available observations (1940-2008). While until the 1990s the decreasing trend of Δ14CO2 was governed by equilibration of the atmospheric bomb 14C perturbation with the oceans and terrestrial biosphere, the largest perturbation today are emissions of 14C-free fossil fuel CO2. This source presently depletes global atmospheric Δ14CO2 by 12-14‰ yr−1, which is partially compensated by 14CO2 release from the biosphere, industrial 14C emissions and natural 14C production. Fossil fuel emissions also drive the changing north-south gradient, showing lower Δ14C in the northern hemisphere only since 2002. The fossil fuel-induced north-south (and also troposphere-stratosphere) Δ14CO2 gradient today also drives the tropospheric Δ14CO2 seasonality through variations of air mass exchange between these atmospheric compartments. Neither the observed temporal trend nor the Δ14CO2 north-south gradient may constrain global fossil fuel CO2 emissions to better than 25%, due to large uncertainties in other components of the (radio)carbon cycle.
Gesehen am 13.03.2023
Im Titel ist die Zahl 14 hochgestellt
Im Titel ist die Zahl 2 tiefgestellt